Land, Letṧema and Leola: Digital Transformation on a Rural Community’s Own Terms - (:unkn) unknown (My University, 2022)
Eurocentric paradigms for technology continue to dominate in Africa yet can impede digital transformation by perpetuating senses of inferiority in societies that have endured colonialism and apartheid. This chapter describes how an African creative pedagogy, Mandhwane, is enabling inhabitants of Mamaila, in rural South Africa, to negotiate the meaning of transformation on their own terms. Since 2018 inhabitants have been establishing their own telecommunications system, or Community Network (CN), to provide local internet access and digital services www.mamailanetwork.co.za/. The CN acts as a “land” where inhabitants freely co-create, which is a vital aspect of Mama Tshepo Khumbane’s philosophy of doing Mandhwane for transformation. The first author applied Matshepo’s techniques to help inhabitants recognise their existing capability to solve their problems by Letṧema, or collective work. Our analysis focuses on designing an app to support Leola, a locally created community scheme in which households collaborate to support bereaved families with funding, equipment and human resources, for funerals and burials. We reflect on the ways that locating design within a rural CN and framing innovation with Mandhwane fosters communal and individualised agency, embeds a social relational ontology in innovation, and can tackle tensions that often arise in digital transformation, such as those that result from differences between older and younger people and between local and externally imposed timescales.
Keywords: African Research